Exenatide Once Weekly Sustained Improvement in Glycemic Control with Weight Loss through 4 Years - Buckley, Rita (MD Conference Express, 2012)
The once-weekly formulation of exenatide, a glucagon-like peptide-1 receptor agonist, is associated with clinically sustained improvement in glycemic control, continued improvements in cardiometabolic risk factors and weight loss after 4 years of treatment in type 2 diabetes mellitus (T2DM) patients. This article discusses results of the open-label extension of the Effects of Exenatide Long-Acting Release on Glucose Control and Safety in Subjects with Type 2 Diabetes Mellitus [DURATION-1; NCT00308139] clinical trial.